Protocol on the hearing of Hafiz Muhamed ef. Pandža in the Department for suppression of anti-state activity of the police area for the City of Zagreb in January 1944 - Jahić, Adnan; Bokun, Edi (Historical Thought, 2025)
This paper provides a translation into Bosnian of a statement signed in the Zagreb police on January 21, 1944 by Hafiz Muhamed ef. Pandža, a member of the Ulema-medžlis in Sarajevo and the initiator of a short-lived Muslim liberation movement which was envisioned as the main military support for Bosnian Muslims in the final days of World War II. The broader military-political context necessary to understand the meaning and content of a given statement is depicted. Although controversial in many ways, the statement is especially illustrative when it comes to the views of the traditional Bosnian Muslim elite of autonomist orientation on military subjects and actors of World War II.